(untitled) (Religious dialogue and cooperation, 2021)
The paper will show the results of a research on the role of religion in the reconciliation process that took place on the territory of Bosnia and Herzegovina from 2012 to 2019. The first part of the paper will show the views of the general population from 2606 respondent. The second part will show a qualitative analysis of the content of the interview with the representatives of three traditional religious communities in Bosnia and Herzegovina. The interview was conducted from the summer of 2018 until spring 2019, with people who are prominent in their public role in society with professors of religious universities, religious school directors and religious teachers who were part of this sample, patrons of Orthodox, Islamic, Roman Catholic, Judaism and Protestant theologians. The results of the survey show that there are potentials for building a stable process of reconciliation. Primarily, the right to choose is for the common good of all citizens of Bosnia and Herzegovina in order to create an atmosphere of acceptance, understanding and respecting differences of members of different national backgrounds and religious traditions. There are many ways to realize the process of reconciliation, and those that are recognized are open dialogue about the past, admitting and apologizing, recognizing the victims and respecting their religious identity, giving special attention to minority groups that feel vulnerable in certain areas. Religion has potentials for reconciliation if their believers accept both the differences and the commonalities of others. Religious leaders, more than lay people, are in a position to contribute to reconciliation.